Prevalence of Helicobacter Pylori in Children with Recurrent Abdominal Pain - Yousaf Kakar, Sana Bushra, Mahdia Babak, Mehboob Ul Haq, Rizwana Kalsoom, Sumaya Fatima, Muhammad Ahtisham Azhar, Muhammad Awais Naseer, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: In children the recurrent abdominal pain is a commonest reason for seeking medical care. In various studies, H pylori and abdominal pain were shown to be significantly correlated in paediatric patients. Objective: To assess the prevalence of helicobacter pylori in children with recurrent abdominal pain Methodology: The current cross sectional study was carried out at the Pediatrics department Sandeman Provincial Hospital Quetta from March 2022 to August 2022. The research included all children with recurrent abdominal pain (according to Rome II criteria) who met the inclusion requirements. Under strict aseptic conditions, five milliliters of blood were taken and sent to the hospital laboratory for ELISA-based H pylori identification. All the information was entered into a predesigned proforma. For the analysis of data, IBM SPSS version 23 was used. Results: In our study, totally 150 children who met the inclusion criteria were enrolled. The male children in our study were 108 (72%) while female children were 32 (28%). The mean age (±SD) was 10 (±4.36) years. Based on ELISA, the helicobacter pylori prevalence was 39 (26%) in children with recurrent abdominal pain. Conclusion: Our study concludes that the in children with recurrent abdominal pain, the helicobacter Pylori prevalence is very high. All the children who visit the pediatrics clinics and having recurrent abdominal pain should be diagnosed for helicobacter pylori. Keywords: Prevalence; helicobacter pylori; children; recurrent abdominal pain